2008
DOI: 10.1002/humu.20712
|View full text |Cite
|
Sign up to set email alerts
|

Novel CCM1, CCM2, and CCM3 mutations in patients with cerebral cavernous malformations: in-frame deletion in CCM2 prevents formation of a CCM1/CCM2/CCM3 protein complex

Abstract: Cerebral cavernous malformations (CCM) are prevalent cerebrovascular lesions predisposing to chronic headaches, epilepsy, and hemorrhagic stroke. Using a combination of direct sequencing and MLPA analyses, we identified 15 novel and eight previously published CCM1 (KRIT1), CCM2, and CCM3 (PDCD10) mutations. The mutation detection rate was >90% for familial cases and >60% for isolated cases with multiple malformations. Splice site mutations constituted almost 20% of all CCM mutations identified. One of these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
114
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 36 publications
6
114
0
Order By: Relevance
“…Similar results have been observed with p.F217A, an engineered mutation (18). In addition, the latest data on a mutant protein lacking, demonstrated that an intact malcavernin domain, located N-terminally of the PTB domain (amino acid residues 11-68), is essential for Krit1 binding to malcavernin (16).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results have been observed with p.F217A, an engineered mutation (18). In addition, the latest data on a mutant protein lacking, demonstrated that an intact malcavernin domain, located N-terminally of the PTB domain (amino acid residues 11-68), is essential for Krit1 binding to malcavernin (16).…”
Section: Introductionsupporting
confidence: 75%
“…It interacts directly with malcavernin independent of Krit1-malcavernin interaction (15). Malcavernin then links Krit1 and PDCD10 which alone would have little affinity with each other (13,16) and directly interacts with PDCD10 in the signalling pathways essential for vascular development and for CCM pathogenesis (13). Moreover, mutations in the PTB domain of malcavernin (amino acids 66-224), on conserved residues critical for NPXY⁄ F motif binding, are deleterious and can lead to inactivation of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…CCMs have been reported in up to 0.5% of the population (16) and are strongly associated with hemorrhagic stroke, seizure, epilepsy, and other focal neurological outcomes. CCMs are also caused by loss of function mutations in CCM2 or CCM3 genes (17), and the CCM2 protein can form the hub of a multiprotein KRIT1-CCM2-CCM3 complex: the CCM complex (12,18,19). Loss of KRIT1, CCM2, or CCM3 proteins is therefore directly associated with focal neurological defects, stroke, and vascular abnormalities.…”
mentioning
confidence: 99%
“…Familial CCM is associated with a heterozygous germline loss-of-function mutation in KRIT1, CCM2 or PDCD10 (Cavalcanti et al, 2012). Malformation development appears to require a local second hit to remove the remaining wild-type copy of the CCM gene (Akers et al, 2009;Dammann et al, 2013;Pagenstecher et al, 2009;Stahl et al, 2008), but other factors in the neurovasculature microenvironment could potentially also have a role in lesion formation (Boulday et al, 2011;Dammann et al, 2013). Local mutations in CCM genes also cause sporadic CCM (Limaye et al, 2009), and there is a growing list of disease-causing mutations, most of which are nonsense mutations leading to a loss of function.…”
Section: Ccm Proteins Krit1mentioning
confidence: 99%
“…CCMs are associated with loss-of-function mutations in any one of the three CCM genes: KRIT1 (Krev interaction trapped 1, also known as CCM1), CCM2 or PDCD10 (programmed cell death 10, also known as CCM3) (Cavalcanti et al, 2012) (see Box 1), suggesting that there is an essential pathway involving all three proteins (Stahl et al, 2008). This hypothesis is bolstered by the knowledge that all three proteins can be found in the same complex within the cell (see below).…”
Section: Introductionmentioning
confidence: 99%